Fouling acorn barnacles in China a review - 曹文浩 严涛 黎祖福 李静 程志强 (Chinese journal of oceanology and limnology, 2013)
We review the species composition, distribution, and seasonal variation of fouling acorn barnacles in Chinese waters--from Bohai Sea and Yellow Sea to East and South China Seas. Thirty-two species of acorn barnacles were found, of which, the dominant species are Amphibalanus amphitrite, A. reticulatus, A. variegates, Balanus trigonus, Fistulobalanus kondakovi, Megabalanus tintinnabulum, Striatobalanus amaryllis, and Eurapha withersi in the fouling communities. A. amphitrite is the dominant species in the coastal waters of Bohai Sea and Yellow Sea and A. reticulatus is dominant in the East and South China Seas. The settlement period of fouling acorn barnacles is usually in summer and autumn. From north to south with the decrease of latitude, their settlement period obviously extends, even to the whole year, and the species number also increases. Other environmental factors, such as salinity and distance from shore, also play an important role in the distribution of fouling acorn barnacles.